Smart City Development Strategy of Wonogiri Regency - Manggalou, Singgih; Azizatun Nafi’ah, Binti; Uang, Yulinda; Dewi, Avela (Publisher Cv. Inara, 2023)
Technology transformation in the smart city concept begins with the implementation of policy transfer to local governments. Wonogiri Regency is one of the districts that implement smart city policy transfer from the central smart city policy. So it is necessary to analyse regional strategies in implementing smart cities. Regional smart city strategy analysis is an analysis carried out to assess the strengths weaknesses opportunities and threats in order to get a picture of the capacity and capability of the region in implementing smart city development programmes. This research aims to analyse the smart city development strategy of Wonogiri Regency. With the regional strategy analysis, Wonogiri Regency can map the right programme according to the dimensions of smart city. So that the implementation of this smart city can run smoothly in accordance with the goals of the Indonesian smart city movement. This study took a locus in Wonogiri Regency, which has a sufficient SPBE index and was chosen to be one of the implementers of the Indonesian smart city movement. Researchers used qualitative methods to analyse the strengths, weaknesses, opportunities and threats of Wonogiri Regency to develop appropriate strategies for these conditions. Researchers found that the smart city strategy is combined with other strategies to solve the problems of the Wonogiri community. The smart city action plan is formed from action plans for smart governance, smart environment, smart society; smart living; smart economy, and smart branding. The action plan must adjust to the strategy formed. The focus of the Action Plan from Wonogiri Regency is to provide integrated services ranging from data to applications.